Nutrient content and gas exchange in calla lily plants grown in a hydroponic system - Landgraf, Paulo Roberto Corrêa; Marques, Douglas José; Mantovani, José Ricardo; Silva, Adriano Bortolotti da; Santos, Breno Régis; Paiva, Patrícia Duarte de Oliveira; Silva, Rodrigo Sérgio da (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the effect of growing calla lily plants (Zantedeschia aethiopica) in a hydroponic system on vegetative growth, nutrient content in shoots, and gas exchange. A completely randomized design in a triple factorial arrangement (2x2x2) was used, with eight treatments, three replicates, and eight plants per plot. The treatments consisted of two dimensions of phenolic foam (2.5x2.5x2.5 and 5.0x5.0x3.8 cm, expressed as height x length x width), two nutrient solutions, and two hydroponic profiles (100 and 150 mm). The calla lily plants were grown in a nutrient film technique (NFT) hydroponic system and presented nutrient content in the shoots in the following decreasing order: K>N>Ca>P>S>Mg for macronutrients and Fe>Mn>Zn>B>Cu for micronutrients. Calla lily plants grown in a NFT hydroponic system, in the phenolic foam of 5.0x5.0x3.8‑cm dimensions and in the hydroponic profile of 150 mm, show greater dry matter accumulation in shoots and bulbs, as well higher photosynthetic rates, regardless of nutrient solution.